AML refractory to primary induction with Ida-FLAG has a poor clinical outcome. (May 2018) - Kavanagh, Simon; Heath, Emily; Hurren, Rose; Gronda, Marcela; Barghout, Samir H.; Liyanage, Sanduni U.; Siriwardena, Thirushi P.; Claudio, Jaime; Zhang, Tong; Sukhai, Mahadeo; Stockley, Tracy L.; Kamel-Reid, Suzanne; et al.
Highlights: Those refractory to Ida-FLAG induction have a dismal prognosis. High risk cytogenetics and TP53 mutations are associated with refractoriness. The dominant genetic mutation persists in patients refractory to Ida-FLAG induction. Abstract: We evaluated outcomes of 100 patients with high risk AML treated with Ida-FLAG induction as first-line therapy. 72 achieved remission with one cycle; 19 did not. High risk cytogenetics and TP53 mutations were associated with failure to achieve remission. In those reaching remission, allogeneic bone marrow transplantation was associated with better relapse-free and overall survival. Those not achieving remission with induction therapy were extremely unlikely to reach remission with further therapy and had a dismal prognosis. Exploratory molecular analysis confirmed persistence of the dominant genetic mutations identified at diagnosis. Ex vivo chemosensitivity did not demonstrate significant differences between responders and non-responders. Thus, Ida-FLAG induction has a high chance of inducing remission in patients with high risk AML. Those achieving remission require allogeneic transplantation to achieve cure; those not achieving remission rarely respond to salvage chemotherapy and have a dismal outcome. Alternatives to conventional chemotherapy must be considered in this group.